Gang Rape: Efforts to Deal with NGO Rifka Annisa in Maqashid Sharia Review - Meri Andani Gang Rape (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Rifka Annisa's Non-Governmental Organization movement in protecting women victims of violence is a form of deep concern for the emergence of a patriarchal culture that strengthens the position of men and weakens the position of women. As a result, women are vulnerable to become victims of violence. The Rifka Annisa movement plays an active role in providing protection to women victims of violence in the form of assistance and prevention. The emergence of the Gang Rape case in public spaces has become a concern for Rifka Annisa in an effort to educate about the prevention of Gang Rape. Seeing from Rifka Annisa's efforts to prevent Gang Rape, it will also be reviewed from Maqasi dSyariah.